2020
DOI: 10.1001/jamacardio.2020.4916
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiovascular Magnetic Resonance Findings in Competitive Athletes Recovering From COVID-19 Infection

Abstract: Myocarditis is a significant cause of sudden cardiac death in competitive athletes and can occur with normal ventricular function. 1 Recent studies have raised concerns of myocardial inflammation after recovery from coronavirus disease 2019 (COVID-19), even in asymptomatic or mildly symptomatic patients. 2 Our objective was to investigate the use of cardiac magnetic resonance (CMR) imaging in competitive athletes recovered from COVID-19 to detect myocardial inflammation that would identify high-risk athletes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
584
5
24

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(641 citation statements)
references
References 6 publications
28
584
5
24
Order By: Relevance
“…While up to 50% of person-to-person transmission of the virus may occur through asymptomatic individuals [10], many people who have been infected with COVID-19 experience significant functional complications within their organ systems. In children and young adults, the disease appears to be mild, but even among previously infected collegiate athletes, potentially life-altering inflammation within the cardiovascular system was detected [11]. Thus, even fit young adults are not immune to the harm that the virus can cause within the human body.…”
Section: Introductionmentioning
confidence: 99%
“…While up to 50% of person-to-person transmission of the virus may occur through asymptomatic individuals [10], many people who have been infected with COVID-19 experience significant functional complications within their organ systems. In children and young adults, the disease appears to be mild, but even among previously infected collegiate athletes, potentially life-altering inflammation within the cardiovascular system was detected [11]. Thus, even fit young adults are not immune to the harm that the virus can cause within the human body.…”
Section: Introductionmentioning
confidence: 99%
“…IRBs are charged with making that assessment, but in the case of human challenge studies, knowledge about infection with SARS-CoV-2 and potential resulting COVID-19 illness continues to evolve; many unknowns remain. Despite the earlier belief that young, healthy adults (the proposed subjects) experience a mild form of COVID-19 and recover quickly, recent data have revealed that this population can experience significant adverse effects when they become infected (22)(23)(24). An additional shortcoming of HCS is that some risks of the vaccine itself may emerge only when a larger number of individuals have been vaccinated.…”
Section: Acceptable Risk-benefitmentioning
confidence: 99%
“…constitute an independent risk factor for COVID-19 mortality [1][2][3][4] . Cardiac MRI studies have suggested that persistent myocardial injury may be more common than appreciated and occur in less severe forms of COVID-19 [5][6][7] . The mechanistic basis by which SARS-CoV-2 results in cardiac dysfunction remains obscure.…”
Section: Introductionmentioning
confidence: 99%